Khitabat Hasan Al-Banna al-shab ila abih : (Dar al-fikr al-Islami)
'Letters of the young Hasan Al-Banna to his father : with a detailed and authenticated biography of the life of the father Shaykh Ahmad Al-Banna' Islam.